A Review of Remote Sensing of Tropical Dry Forests (Tropical Dry Forests in the Americas, 2014)
For more than 20 years, tropical dry forests (TDFs) have been recognized among the world’s most threatened ecosystems (Murphy and Lugo 1986b; Janzen 1988a; Olson 2000). These forests account for 49% of the vegetated land cover in Mesoamerica and the Caribbean and 42% of all tropical forest vege tation worldwide (Murphy and Lugo 1995; Van Bloem et al. 2004) with a current estimated total global cover of 1,048,700 km2 (Miles et al. 2006); they often are areas of intense human occupation and exploitation (Murphy and Lugo 1986a; Quesada and Stoner 2004; Sánchez-Azofeifa et al. 2005a). In spite of this, these forests have been the subject of only a fraction of the research devoted to tropical forests globally, with the majority of studies over the past 60 years having focused on tropical humid forests or rain forests (SánchezAzofeifa et al. 2005b). With increasing concern over the health and conservation status of TDFs (Stoner and Sánchez-Azofeifa 2009), there is a need for tools to better map and understand these important resources.